“You are next in line”: Moving down the Line(s) with Ron Padgett - Olivier Brossard (Transatlantica)
“No ideas but in hinges,” poet Stephen Rodefer once quipped in his poem “Numberless Shadows,” playfully modifying William Carlos Williams’s famous line. This essay examines line breaks as poetic hinges in the work of Ron Padgett: they are flexible spaces where the parts of the poem turn and articulate, the lines poised between conflicting forces, between formal interruption and syntactical momentum. An attempt at defining such versatile spaces, this essay seeks to explore line breaks as the pretexts for Ron Padgett’s metatextual poetics. Line breaks are pivotal points: not only are they constitutive of verse, but they also provide occasions for the poem to reflect upon itself. In Padgett’s work, they are critical junctures, when language hesitates between transitive and intransitive impulses.